Perceptions of Professionalism Among Nursing Faculty and Nursing Students. (February 2013) - Akhtar-Danesh, Noori; Baumann, Andrea; Kolotylo, Camille; Lawlor, Yvonne; Tompkins, Catherine; Lee, Ruth
Although there is no consensus about the definition of professionalism, some generally recognized descriptors include knowledge, specialization, intellectual and individual responsibility, and well-developed group consciousness. In this study, Q-methodology was used to identify common viewpoints about professionalism held by nursing faculty and students, and four viewpoints emerged as humanists, portrayers, facilitators, and regulators . The humanists reflected the view that professional values include respect for human dignity, personal integrity, protection of patient privacy, and protection of patients from harm. The portrayers believed that professionalism is evidenced by one's image, attire, and expression. For facilitators, professionalism not only involves standards and policies but also includes personal beliefs and values. The regulators believed that professionalism is fostered by a workplace in which suitable beliefs and standards are communicated, accepted, and implemented by its staff. The differences indicate that there may be numerous contextual variables that affect individuals' perceptions of professionalism.